2013
DOI: 10.1371/journal.pone.0069974
|View full text |Cite
|
Sign up to set email alerts
|

Threonine Affects Intestinal Function, Protein Synthesis and Gene Expression of TOR in Jian Carp (Cyprinus carpio var. Jian)

Abstract: This study aimed to investigate the effects of threonine (Thr) on the digestive and absorptive ability, proliferation and differentiation of enterocytes, and gene expression of juvenile Jian carp (Cyprinus carpio var. Jian). First, seven isonitrogenous diets containing graded levels of Thr (7.4–25.2 g/kg diet) were fed to the fishes for 60 days. Second, enterocyte proliferation and differentiation were assayed by culturing enterocytes with graded levels of Thr (0–275 mg/l) in vitro. Finally, enterocytes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 89 publications
14
63
1
Order By: Relevance
“…In this study, data firstly showed that optimal ETSP in the low-protein diet downregulated 4E-BP2 mRNA levels in PI, MI, and DI, which showed a contrary tendency to that of TOR. Previous studies from our laboratory showed that intestinal 4E-BP2 gene expression also showed a contrary tendency as that of TOR towards dietary threonine (Feng et al 2013) and isoleucine (Zhao et al 2012). However, the reasons for these changes are unknown, since there is no other information about the effect of ETSP on fish TOR and 4E-BP2 gene expressions.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, data firstly showed that optimal ETSP in the low-protein diet downregulated 4E-BP2 mRNA levels in PI, MI, and DI, which showed a contrary tendency to that of TOR. Previous studies from our laboratory showed that intestinal 4E-BP2 gene expression also showed a contrary tendency as that of TOR towards dietary threonine (Feng et al 2013) and isoleucine (Zhao et al 2012). However, the reasons for these changes are unknown, since there is no other information about the effect of ETSP on fish TOR and 4E-BP2 gene expressions.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, silvery‐black porgy juveniles fed the threonine‐deficient diet (1.12% DM) had the lowest survival rates, which may be attributed to some physiological and metabolic dysfunctions in this experimental group. In this context, it has been reported that threonine is involved in many physiological and biochemical processes, including somatic growth, feed efficiency, digestive and absorptive, gene expression regulation, antioxidant and immune functions in different fish species (Gao Feng et al., ; Habte‐Tsion, Ge, et al., , Habte‐Tsion, Liu, et al., , Habte‐Tsion, Ren, et al., , Habte‐Tsion, Ren, Liu, Xie, et al., , Habte‐Tsion et al., ). Moreover, along with arginine‐ (1.73% DM) and lysine (1.29% DM)‐deficient diets, all immunological parameters were lower in fish fed the threonine‐deficient diet than in the other groups, which indicated its significant role in fish health.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, information regarding the effect of leucine on TOR and S6K1 is limited in fish. Studies from our laboratory showed that arginine (Wang et al, 2015) and threonine (Feng et al, 2013a) regulated the gene transcription of TOR in the muscle of Jian carp. These data show that there may be a close relationship between leucine and TOR/S6K1 in fish muscle, which warrants investigation.…”
Section: Introductionmentioning
confidence: 95%